Process for the production of a polypropylene insulated low voltage power cable
Patent Information
- Application Number
- CN202611178609.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-05
- Publication Date
- 2026-10-30
AI Technical Summary
[0002]当前0.6/1kV低压电力电缆多采用圆形绞合导体,并在绞合导体表面挤出成型绝缘层形成第一道保护,绝缘层厚度对产品的电气强度、机械防护性、耐环境侵蚀性等具有重要意义,但同时也限制了导体的散热效率,并且挤出后绝缘层包覆在导体表面发生冷却时,由于内外温差会较大,外层先固化定型后,会对内层形成径向拉应力和轴向残余应力,导致内层在冷却固化过程中沿径向向内的收缩受阻,从而易在导体-绝缘界面处形成微隙或剥离趋势,影响层间结合力,增加界面接触热阻
另一方面,本申请将导体外表面粗糙度处理至明显低于常规导体所要求的Ra为1.6~3.2um,使光滑且密实的导体外表面与绝缘层之间在高温挤塑过程中形成紧密的分子级贴合界面,使该界面接触热阻有效降低,提高了导热散热效果。并且绝缘层中的无机填料虽经过硅烷偶联剂表面处理,但依然存在一定趋势会向靠近绝缘层表面迁移,而本申请中认为:可能同样是基于导体表面光滑并与绝缘层之间的界面分子级贴合,使迁移至靠近绝缘层内表面的那小部分无机填料于该处的分布排列明显更为整齐、有序,并进一步通过这部分无机填料影响该处聚合物大分子冷却过程中的晶相变化,使其能更好抵抗住绝缘层外层优先冷却定型后对其所产生的向外径向拉应力。因此虽然导体表面的光滑程度有明显提升,表面摩擦力明显减小,但依然能有效确保绝缘层与导体表面之间的结合,从而能在十分光滑的导体表面有效增加挤包上去的绝缘层厚度,自然也有利于电气稳定性和电缆使用寿命。
Smart Images

Figure CN123017641A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of low-voltage power cable technology, and specifically relates to a method for preparing a polypropylene insulated low-voltage power cable. Background Technology
[0002] Currently, most 0.6 / 1kV low-voltage power cables use round stranded conductors, with an insulation layer extruded onto the surface of the stranded conductor to form the first layer of protection. The thickness of the insulation layer is important for the electrical strength, mechanical protection, and resistance to environmental corrosion of the product. However, it also limits the heat dissipation efficiency of the conductor. Furthermore, when the insulation layer is wrapped around the conductor surface and cools after extrusion, the large temperature difference between the inside and outside causes the outer layer to solidify first, resulting in radial tensile stress and axial residual stress on the inner layer. This hinders the radial inward shrinkage of the inner layer during the cooling and solidification process, making it easy to form micro-gaps or peeling tendencies at the conductor-insulation interface, affecting the interlayer bonding force and increasing the interfacial contact thermal resistance. Summary of the Invention
[0003] To solve the above-mentioned technical problems, the present invention provides a method for preparing a polypropylene insulated low-voltage power cable, comprising: (1) The surface of the stranded conductor is treated to make the surface roughness Ra of the outer surface of the stranded conductor ≤ 0.8 μm; The stranded conductor is made of copper or aluminum monofilaments with trapezoidal cross-sections. The stranding is carried out in layers with concentric stranding and the stranding direction is opposite between adjacent layers. The copper or aluminum monofilaments are monofilaments with trapezoidal cross-sections obtained by continuous extrusion or precision rolling of blank copper rods or blank aluminum rods. The width ratio of the upper and lower bases of the monofilaments is controlled between 1:1.5 and 1:2.5. Before surface treatment, the stranded conductor is first conveyed through a roller pressing and forming equipment to achieve radial compression, so that the contact surface between adjacent single wires in the stranded conductor changes from conventional point contact / line contact to planar contact or near-planar contact. This compacts the stranding gap, stabilizes the conductor structure to prevent fraying, increases the conductor fill factor, reduces the conductor outer diameter, improves the conductor surface quality, uniformizes the thickness of the subsequent insulation layer, reduces AC loss, and improves heat dissipation performance. Ultimately, this results in reducing cable size, reducing material consumption, and improving the electrical performance and mechanical reliability of the cable. The surface treatment operation is performed by using a wire brush roller or a polishing wheel; (2) An insulating layer of 1.6 to 2 mm thickness is extruded onto the surface of the stranded conductor after step (1). The insulating layer, by weight, includes 55 to 75 parts of isotactic polypropylene, 15 to 30 parts of propylene-ethylene copolymer elastomer, 3 to 5 parts of maleic anhydride grafted polypropylene, 0.8 to 1.5 parts of antioxidant, and 2 to 12 parts of thermally conductive insulating filler. An insulating layer is formed by co-extrusion using two single-screw extruders. In the two single-screw extruders, the inner layer melt of the insulating layer is extruded through the first extruder. The inner layer melt of the insulating layer, calculated by weight, includes 55-75 parts of isotactic polypropylene, 15-30 parts of propylene-ethylene copolymer elastomer, 3-5 parts of maleic anhydride grafted polypropylene, 0.8-1.5 parts of antioxidant, and 2-4 parts of thermally conductive and insulating filler. The barrel temperature of the first extruder is 165-190℃, and the extrusion line speed is 15-25m / min. The outer layer melt of the insulation layer is extruded through a second extruder. The outer layer melt of the insulation layer includes, by weight, 55-75 parts of isotactic polypropylene, 15-30 parts of propylene-ethylene copolymer elastomer, 3-5 parts of maleic anhydride grafted polypropylene, 0.8-1.5 parts of antioxidant, and 4-12 parts of thermally conductive and insulating filler. The barrel temperature of the second extruder is 165-185℃, and the extrusion line speed is 15-25m / min. After being preheated to 120°C following step (1), the stranded conductor enters the co-extrusion die. The inner and outer melts of the extruded insulation layer are then combined at approximately 15mm from the die tip using a flow distributor, forming a double-layer co-extrusion package with a thickness ratio of 1:1. The die temperature is 180–190°C. After extrusion, the package undergoes segmented cooling: the first cooling medium is warm water at 60–65°C, and the second cooling medium is ambient cold water at 25°C. Finally, the insulation layer formed outside the stranded conductor can be further divided radially from the inside out into: Inner layer near the conductor (approximately 35% of the radial thickness of the insulation layer): The filler content is relatively low, which is intended to avoid the degradation of the intrinsic high volume resistivity and low dielectric constant of polypropylene by high content of rigid inorganic fillers, and to ensure the long-term electrical safety and flexibility of the insulation in high electric field regions. Intermediate transition layer (approximately 30% of the radial thickness of the insulation layer): The filler content is between that of the outer layer near the sheath below. The appearance of this intermediate transition layer is achieved based on the co-extrusion process of two extruders: Since the inner layer melt and the outer layer melt of the insulation layer have the same polypropylene matrix, the only difference between the two is the content of thermally conductive and insulating filler. Therefore, when the two layers of melt meet at the co-extrusion die, the molecular chains at the interface diffuse and entangle with each other, thus naturally forming a continuous gradient transition zone of filler concentration, rather than an abrupt interface. The outer layer near the sheath (approximately 35% of the radial thickness of the insulation layer): contains a relatively large amount of filler. Taking advantage of the fact that the electric field strength in this area has been greatly reduced, the filler content can be appropriately increased to construct an efficient radial heat conduction path.
[0004] The thermally conductive insulating filler is a hexagonal boron nitride / fumed silica composite filler with a silane coupling agent surface treatment. The hexagonal boron nitride has a thermal conductivity of up to 300-400 W / (m·K) along its own planar direction, and the large aspect ratio of the sheets forms long-range thermally conductive channels in the insulating layer. At the same time, fumed silica nanoparticles fill the gaps between the hexagonal boron nitride sheets to form bridging thermally conductive nodes, effectively connecting the thermally conductive pathways between the sheets, thereby constructing a highly efficient thermally conductive network. On the other hand, this application processes the outer surface roughness of the conductor to a level significantly lower than the Ra value required for conventional conductors (1.6~3.2 μm). This allows a smooth and dense outer surface of the conductor to form a tight molecular-level bonding interface with the insulation layer during high-temperature extrusion, effectively reducing the interface thermal resistance and improving heat conduction and dissipation. Furthermore, although the inorganic filler in the insulation layer undergoes surface treatment with a silane coupling agent, it still tends to migrate closer to the surface of the insulation layer. This application suggests that, similarly, the smooth conductor surface and the molecular-level bonding between it and the insulation layer result in a more orderly and systematic distribution of the small portion of inorganic filler that migrates closer to the inner surface of the insulation layer. This inorganic filler further influences the phase change of the polymer macromolecules during cooling, enabling the filler to better resist the outward radial tensile stress generated after the outer layer of the insulation layer preferentially cools and solidifies. Therefore, although the smoothness of the conductor surface is significantly improved and the surface friction is significantly reduced, the bonding between the insulation layer and the conductor surface can still be effectively ensured. This allows for an effective increase in the thickness of the extruded insulation layer on a very smooth conductor surface, which is naturally beneficial to electrical stability and cable lifespan. Attached Figure Description
[0005] Figure 1 This is a schematic diagram of the layer structure of the finished cable finally prepared in Embodiment 3 of the present invention. Detailed Implementation
[0006] 36 parts by weight of flake boron nitride with a diameter of 10-15 μm and 2 parts by weight of fumed silica with a particle size of 60-80 nm were mixed and stirred at 1800 rpm for 1 min. Then, 40 parts by weight of silane solution, which was uniformly mixed from 70 wt% ethanol, 15 wt% water and 15 wt% KH560, were sprayed on top. After spraying, the mixture was stirred and rolled at 1500 rpm for 1 min and then dried in an oven at 105 °C for 90 min. After cooling in the oven, the resulting hexagonal boron nitride / fumed silica composite filler with silane coupling agent surface treatment was used as a thermally conductive and insulating filler. Example 1
[0007] (1) The stranded conductor is supported by a circular aluminum alloy wire with a diameter of 2.85 mm as the center, and is paired with three layers of fan-shaped trapezoidal pressed aluminum alloy strands that are stranded in opposite directions: the inner layer has 5 strands with a height of 2.08 mm stranded to the left, the middle layer has 10 strands with a height of 2.30 mm stranded to the right, and the outer layer has 14 strands with a height of 2.33 mm stranded to the left. Each layer of aluminum alloy strands is pre-stretched separately and pressed by a mold. After the layer stranding is completed, the whole is re-pressed twice to make a stranded conductor with a nominal area of 185 mm². The conductor is then treated with an online polishing wheel until the outer surface roughness Ra is 0.6 μm. (2) 75 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 20 parts by weight of 3745P propylene-ethylene copolymer elastomer, 4 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 4 parts by weight of the above-obtained thermally conductive and insulating filler are melt-blended and extruded in a first extruder as the inner layer melt of the insulating layer. The barrel temperature of the first extruder is 165-190℃ and the extrusion line speed is 20m / min. 75 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 20 parts by weight of 3745P propylene-ethylene copolymer elastomer, 4 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 10 parts by weight of the above-obtained thermally conductive and insulating filler were melt-blended and extruded in a second extruder as the outer melt of the insulating layer. The barrel temperature of the second extruder was 165-185℃, and the extrusion line speed was 20m / min. After being preheated to 120°C following step (1), the stranded conductor enters the co-extrusion die. The inner and outer melts of the extruded insulation layer are then combined at approximately 15 mm from the die tip using a flow channel distributor to form a double-layer co-extrusion package with a thickness ratio of 1:1. The die temperature is 185°C. After extrusion, the package undergoes segmented cooling: the first cooling medium is 60°C warm water for 60 seconds; the second cooling medium is 25°C room temperature cold water for 60 seconds. After drying, the package is subjected to online annealing with ultraviolet laser (wavelength 355nm, power density 10J / cm², scanning overlap rate 40%) to eliminate residual stress and form micro-crosslinking protection on the surface, thus finally obtaining an insulation layer with a total thickness of 2.4 mm on the outer surface of the stranded conductor. Example 2
[0008] (1) The stranded conductor is supported by a circular aluminum alloy wire with a diameter of 2.85 mm as the center, and is paired with three layers of fan-shaped trapezoidal pressed aluminum alloy strands that are stranded in opposite directions: the inner layer has 5 strands with a height of 2.08 mm stranded to the left, the middle layer has 10 strands with a height of 2.30 mm stranded to the right, and the outer layer has 14 strands with a height of 2.33 mm stranded to the left. Each layer of aluminum alloy strands is pre-stretched separately and pressed by a mold. After the layer stranding is completed, the whole is re-pressed twice to make a stranded conductor with a nominal area of 185 mm². The conductor is then treated with an online polishing wheel until the outer surface roughness Ra is 0.6 μm. (2) 68 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 17 parts by weight of 3745P propylene-ethylene copolymer elastomer, 3 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 2 parts by weight of the above-obtained thermally conductive and insulating filler are melt-blended and extruded in a first extruder as the inner layer melt of the insulating layer. The barrel temperature of the first extruder is 165-190℃ and the extrusion line speed is 18m / min. 68 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 17 parts by weight of 3745P propylene-ethylene copolymer elastomer, 3 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 7 parts by weight of the above-obtained thermally conductive and insulating filler were melt-blended and extruded in a second extruder as the outer melt of the insulating layer. The barrel temperature of the second extruder was 165-185℃, and the extrusion line speed was 18m / min. After being preheated to 120°C following step (1), the stranded conductor enters the co-extrusion die. The inner and outer melts of the extruded insulation layer are then combined at approximately 15 mm from the die tip using a flow channel distributor to form a double-layer co-extrusion package with a thickness ratio of 1:1. The die temperature is 185°C. After extrusion, the package undergoes segmented cooling: the first cooling medium is 60°C warm water for 60 seconds; the second cooling medium is 25°C room temperature cold water for 60 seconds. After drying, the package is subjected to online annealing with ultraviolet laser (wavelength 355nm, power density 10J / cm², scanning overlap rate 40%) to eliminate residual stress and form micro-crosslinking protection on the surface, thus finally obtaining an insulation layer with a total thickness of 2.3 mm on the outer surface of the stranded conductor. Example 3
[0009] (1) The stranded conductor is supported by a circular aluminum alloy wire with a diameter of 2.85 mm as the center, and is paired with three layers of fan-shaped trapezoidal pressed aluminum alloy strands that are stranded in opposite directions: the inner layer has 5 strands with a height of 2.08 mm stranded to the left, the middle layer has 10 strands with a height of 2.30 mm stranded to the right, and the outer layer has 14 strands with a height of 2.33 mm stranded to the left. Each layer of aluminum alloy strands is pre-stretched separately and pressed by a mold. After the layer stranding is completed, the whole is re-pressed twice to make a stranded conductor with a nominal area of 185 mm². The conductor is then treated with an online polishing wheel until the outer surface roughness Ra is 0.6 μm. (2) 60 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 15 parts by weight of 3745P propylene-ethylene copolymer elastomer, 3 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 0.8 parts by weight of antioxidant 1076, and 2 parts by weight of the above-obtained thermally conductive and insulating filler are melt-blended and extruded in a first extruder as the inner layer melt of the insulating layer. The barrel temperature of the first extruder is 165-190℃ and the extrusion line speed is 22m / min. 60 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 15 parts by weight of 3745P propylene-ethylene copolymer elastomer, 3 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 0.8 parts by weight of antioxidant 1076, and 6 parts by weight of the above-obtained thermally conductive and insulating filler were melt-blended and extruded in a second extruder as the outer melt of the insulating layer. The barrel temperature of the second extruder was 165-185℃, and the extrusion line speed was 22m / min. After being preheated to 120°C following step (1), the stranded conductor enters the co-extrusion die. The inner and outer melts of the extruded insulation layer are then combined at approximately 15 mm from the die tip using a flow channel distributor to form a double-layer co-extrusion package with a thickness ratio of 1:1. The die temperature is 185°C. After extrusion, the package undergoes segmented cooling: the first cooling medium is 60°C warm water for 60 seconds; the second cooling medium is 25°C room temperature cold water for 60 seconds. After drying, the package is subjected to online annealing with ultraviolet laser (wavelength 355nm, power density 10J / cm², scanning overlap rate 40%) to eliminate residual stress and form micro-crosslinking protection on the surface, thus finally obtaining an insulation layer with a total thickness of 2.5 mm on the outer surface of the stranded conductor.
[0010] (3) Fill the gap between the three insulated wire cores obtained in step (2) with polypropylene mesh filling rope, and ensure the roundness of the cable. Then wrap the cable evenly with halogen-free flame-retardant wrapping tape with a wrapping overlap rate of 20% to form an overall binding and protection. (4) After the LSZH granules are dried at 80°C for 4 hours, they are extruded onto the outside of the halogen-free flame-retardant wrapping layer on the cable obtained in step (3) by a single screw extruder. The barrel temperature of the single screw extruder is 140-175°C, the die temperature is 170°C, and the extrusion line speed is 12m / min. After extrusion, the inner sheath layer with a thickness of 1.2mm is obtained by cooling in a room temperature water bath and drying. (5) A steel wire armoring machine is used to perform single-layer leftward twisting on the surface of the inner sheath layer obtained in step (4) to form an armor layer. The diameter of the galvanized steel wire is 2.5 mm, the total number of wires is 48, the twisting pitch ratio is 12 times, the tension of a single steel wire is controlled at 180±10N, and the total thickness of the armor layer is 5.0 mm. (6) A layer of halogen-free flame-retardant wrapping tape is wrapped around the armor layer obtained in step (5) as a buffer liner. The halogen-free flame-retardant wrapping tape is 40mm wide, 0.2mm thick, with a wrapping overlap rate of 15% and a wrapping tension of 5N. The wrapping direction is opposite to the twisting direction of the armor steel wire in step (5). The halogen-free flame-retardant wrapping tape is tightly and flatly attached to the surface of the armor layer. (7) After the LSZH granules are dried at 80°C for 4 hours, they are extruded onto the outside of the buffer liner in step (6) using a single-screw extruder. The barrel temperature of the single-screw extruder is 140-175°C, the die temperature is 170°C, and the extrusion line speed is 12m / min. After extrusion, the granules are cooled in a room temperature water bath and dried to obtain the outer sheath layer, thus completing the preparation of the finished cable. The layer structure of the cable is as follows: Figure 1 As shown. Comparative Example 1
[0011] In step (1), the surface of the stranded conductor after compaction was not treated with a polishing wheel; all other operations were the same as in Example 1. (1) The stranded conductor is supported by a circular aluminum alloy wire with a diameter of 2.85 mm as the center, and is paired with three layers of fan-shaped trapezoidal pressed aluminum alloy strands twisted in opposite directions: the inner layer has 5 strands with a height of 2.08 mm twisted to the left, the middle layer has 10 strands with a height of 2.30 mm twisted to the right, and the outer layer has 14 strands with a height of 2.33 mm twisted to the left. Each layer of aluminum alloy strands is pre-stretched separately and pressed by a mold. After the layered stranding is completed, the whole is re-pressed twice to make a stranded conductor with a nominal area of 185 mm². The surface of the stranded conductor is cleaned to the point of being free of oxide components, but the surface roughness Ra is 2 μm. (2) 75 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 20 parts by weight of 3745P propylene-ethylene copolymer elastomer, 4 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 4 parts by weight of the above-obtained thermally conductive and insulating filler are melt-blended and extruded in a first extruder as the inner layer melt of the insulating layer. The barrel temperature of the first extruder is 165-190℃ and the extrusion line speed is 20m / min. 75 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 20 parts by weight of 3745P propylene-ethylene copolymer elastomer, 4 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 10 parts by weight of the above-obtained thermally conductive and insulating filler were melt-blended and extruded in a second extruder as the outer melt of the insulating layer. The barrel temperature of the second extruder was 165-185℃, and the extrusion line speed was 20m / min. After being preheated to 120°C following step (1), the stranded conductor enters the co-extrusion die. The inner and outer melts of the extruded insulation layer are then combined at approximately 15 mm from the die tip using a flow channel distributor to form a double-layer co-extrusion package with a thickness ratio of 1:1. The die temperature is 185°C. After extrusion, the package undergoes segmented cooling: the first cooling medium is 60°C warm water for 60 seconds; the second cooling medium is 25°C room temperature cold water for 60 seconds. After drying, the package is subjected to online annealing with ultraviolet laser (wavelength 355nm, power density 10J / cm², scanning overlap rate 40%) to eliminate residual stress and form micro-crosslinking protection on the surface, thus finally obtaining an insulation layer with a total thickness of 2.4 mm on the outer surface of the stranded conductor. Comparative Example 2
[0012] The inner layer melt of the insulating layer in step (2) does not contain any thermally conductive insulating filler, and the remaining operations are the same as in Example 1: (1) The stranded conductor is supported by a circular aluminum alloy wire with a diameter of 2.85 mm as the center, and is paired with three layers of fan-shaped trapezoidal pressed aluminum alloy strands that are stranded in opposite directions: the inner layer has 5 strands with a height of 2.08 mm stranded to the left, the middle layer has 10 strands with a height of 2.30 mm stranded to the right, and the outer layer has 14 strands with a height of 2.33 mm stranded to the left. Each layer of aluminum alloy strands is pre-stretched separately and pressed by a mold. After the layer stranding is completed, the whole is re-pressed twice to make a stranded conductor with a nominal area of 185 mm². The conductor is then treated with an online polishing wheel until the outer surface roughness Ra is 0.6 μm. (2) 75 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 20 parts by weight of 3745P propylene-ethylene copolymer elastomer, 4 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, and 1 part by weight of antioxidant 1076 are melt-blended and extruded in the first extruder as the inner layer melt of the insulation layer. The barrel temperature of the first extruder is 165-190℃ and the extrusion line speed is 20m / min. 75 parts by weight of Yanshan Petrochemical 1396D isotactic polypropylene, 20 parts by weight of 3745P propylene-ethylene copolymer elastomer, 4 parts by weight of PO1015 maleic anhydride grafted polypropylene compatibilizer, 1 part by weight of antioxidant 1076, and 10 parts by weight of the above-obtained thermally conductive and insulating filler were melt-blended and extruded in a second extruder as the outer melt of the insulating layer. The barrel temperature of the second extruder was 165-185℃, and the extrusion line speed was 20m / min. After being preheated to 120°C following step (1), the stranded conductor enters the co-extrusion die. The inner and outer melts of the extruded insulation layer are then combined at approximately 15 mm from the die tip using a flow channel distributor to form a double-layer co-extrusion package with a thickness ratio of 1:1. The die temperature is 185°C. After extrusion, the package undergoes segmented cooling: the first cooling medium is 60°C warm water for 60 seconds; the second cooling medium is 25°C room temperature cold water for 60 seconds. After drying, the package is subjected to online annealing with ultraviolet laser (wavelength 355nm, power density 10J / cm², scanning overlap rate 40%) to eliminate residual stress and form micro-crosslinking protection on the surface, thus finally obtaining an insulation layer with a total thickness of 2.4 mm on the outer surface of the stranded conductor. Comparative Example 3
[0013] In step (1), the stranded conductor after compaction was not treated with a polishing wheel. Therefore, although the surface of the stranded conductor was clean and free of oxidizing components, the surface roughness Ra was 2 μm. The remaining operations were the same as in Example 2. Comparative Example 4
[0014] The inner layer melt of the insulating layer in step (2) does not contain any thermally conductive insulating filler, and the rest of the operation is the same as in Example 2.
[0015] The peel strength of the insulated wire cores prepared in step (2) of each of the above embodiments and step (2) of the comparative embodiment was tested respectively: First, a 20cm long sample was cut from the middle section of the insulated wire core. At the end of the sample, the insulation layer was carefully cut and peeled off from the surface of the stranded conductor to a length of about 2cm as the clamping part during the test. The width of the clamping part was about 1cm. It was ensured that the insulation layer used as the clamping part was completely separated from the stranded conductor when it was cut and peeled off. The sample treated as above was installed on a universal material testing machine of model CMT6104. The testing machine clamped the clamping part and the corresponding stranded conductor section respectively. The peeling test was carried out at room temperature of about 25°C using the 180° peeling method. The peeling speed was controlled at 50±5mm / min. The average load during the peeling process was recorded and the peel strength was calculated as shown in Table 1.
[0016] Table 1 .
[0017] As can be seen from Table 1, compared with Comparative Example 1 and Comparative Example 3, in Example 1, the adhesion of the extruded insulation layer to the stranded conductor did not decrease significantly, and even increased, despite the significantly reduced surface roughness of the stranded conductor. Therefore, the applicant has reason to believe that this is because when the surface of the stranded conductor becomes smooth to a certain extent, it can form a large-scale interface molecular-level adhesion with the insulation layer. This makes the distribution and arrangement of the small portion of inorganic filler that migrates to the inner surface of the insulation layer more orderly and systematic. Furthermore, this portion of inorganic filler affects the crystal phase change of the polymer macromolecules during the cooling process, enabling it to better resist the outward radial tensile stress generated by the preferential cooling and shaping of the outer layer of the insulation layer. Correspondingly, this effectively ensures the bonding between the insulation layer and the stranded conductor. Therefore, a thicker insulation layer can be extruded on such a smooth conductor surface as protection. The insulation layer thickness is significantly improved compared to the "conventional insulation layer thickness of 1.6 mm required for a 185 mm² stranded conductor". In Comparative Examples 1 and 3, the stranded conductor surface has a certain roughness, which is indeed beneficial to the bonding of the insulation layer. However, the presence of roughness makes the micro-interface uneven, which greatly hinders the formation of interfacial molecular-level bonding between the stranded conductor surface and the insulation layer. As a result, the inorganic filler cannot be arranged in an orderly manner near the interface, thus affecting the crystal phase of the polymer matrix at the interface. Consequently, it cannot effectively resist the outward radial tensile stress generated after the outer layer of the insulation layer is cooled. In the end, the bonding effect of the insulation layer is not as ideal as that of this solution. The above analysis also shows from Comparative Examples 2 and 4 that: in Comparative Examples 2 and 4, when no inorganic filler was added to the inner layer of the insulation layer near the stranded conductor, the bonding effect was significantly reduced when the polymer was bonded to the very smooth stranded conductor. This is also because there was no orderly arrangement and distribution of inorganic filler, so it could not affect the polymer crystal phase. Similarly, in both Example 1 and Example 2, the proportion of inorganic filler in the inner layer of the insulating layer is significantly greater in Example 1 than in Example 2. Therefore, Example 1 has a more sufficient influence on the crystal phase of the polymer near the interface during cooling, ultimately making the bonding effect between the conductor and the insulating layer even more ideal than that of a rough conductor surface, while Example 2 currently only achieves an effect close to that of a rough conductor surface.
Claims
1. A method for preparing a polypropylene insulated low-voltage power cable, characterized in that: The preparation method includes, (1) The stranded conductor is surface treated so that the surface roughness Ra of the outer surface of the stranded conductor is ≤0.8μm; (2) An insulating layer of 1.6 to 2 mm thickness is extruded onto the surface of the stranded conductor after the treatment in step (1). The insulating layer comprises, by weight, 55 to 75 parts of isotactic polypropylene, 15 to 30 parts of propylene-ethylene copolymer elastomer, 3 to 5 parts of maleic anhydride grafted polypropylene, 0.8 to 1.5 parts of antioxidant, and 2 to 12 parts of thermally conductive insulating filler.
2. The method for preparing polypropylene insulated low-voltage power cable as described in claim 1, characterized in that: The stranded conductor mentioned in step (1) is made of copper or aluminum monofilaments with trapezoidal cross-sections. The stranding is carried out in layers with concentric stranding and the stranding direction between adjacent layers is opposite. The width ratio of the upper and lower bases of the trapezoidal cross-section is 1:1.5 to 1:2.
5.
3. The method for preparing polypropylene insulated low-voltage power cable as described in claim 1, characterized in that: In step (1), before the surface treatment is performed, the stranded conductor is transferred through a roller pressing and forming equipment to achieve radial pressing.
4. The method for preparing polypropylene insulated low-voltage power cable as described in claim 1, characterized in that: The surface treatment described in step (1) is performed by using a wire brush roller or a polishing wheel.
5. The method for preparing polypropylene insulated low-voltage power cable as described in claim 1, characterized in that: The thermally conductive and insulating filler mentioned in step (2) is a hexagonal boron nitride / fumed silica composite filler that has been surface-treated with silane coupling agent.
6. The method for preparing polypropylene insulated low-voltage power cable as described in claim 1, characterized in that: In step (2), the insulating layer is formed by co-extrusion using two single-screw extruders. In the two single-screw extruders, the inner layer melt of the insulating layer is extruded by the first extruder, and the outer layer melt of the insulating layer is extruded by the second extruder. The inner layer melt of the insulating layer comprises, by weight, 55-75 parts of isotactic polypropylene, 15-30 parts of propylene-ethylene copolymer elastomer, 3-5 parts of maleic anhydride-grafted polypropylene, 0.8-1.5 parts of antioxidant, and 2-4 parts of thermally conductive insulating filler. The outer melt of the insulating layer comprises, by weight, 55-75 parts of isotactic polypropylene, 15-30 parts of propylene-ethylene copolymer elastomer, 3-5 parts of maleic anhydride-grafted polypropylene, 0.8-1.5 parts of antioxidant, and 4-12 parts of thermally conductive insulating filler.
7. The method for preparing polypropylene insulated low-voltage power cable as described in claim 6, characterized in that: In step (2), the barrel temperature of the first extruder is 165-190℃, the barrel temperature of the second extruder is 165-185℃, and the extrusion line speed of both the first extruder and the second extruder is 15-25m / min.
8. The method for preparing polypropylene insulated low-voltage power cable as described in claim 6, characterized in that: In step (2), the stranded conductor, after being preheated following the treatment in step (1), enters the co-extrusion die. The inner layer melt and the outer layer melt of the insulation layer converge at the front end of the die through the flow channel distributor to form a double-layer co-extrusion package, which is then cooled in stages.
